(untitled) (Historia, 2021)
English This article examines in depth the reaction of the British government and the British press to the election of a National Party, apartheid government in South Africa in May 1948. The conventional view – that the 1948 election represented a “turning point” in South African history and Anglo-South African relations – is repudiated. On the contrary, it appears that the British, although they almost uniformly admired Field Marshal Smuts and distrusted Afrikaner Nationalists, felt that the results of the 1948 election were not indicative of a fundamental shift. The view was widespread in Britain and South Africa that Smuts and the United Party would soon be returned to power, and apartheid would prove to be impractical and politically embarrassing to the Nationalists. Only after Smuts’s death in 1950, and after the further consolidation of National Party political control in South Africa, did the British begin to accept that the re-establishment of a mildly progressive, anglophile regime in South Africa was unlikely to occur. Afrikaans Die vurk in die pad? Britse reaksies op die verkiesing van ’n apartheidregering in Suid-Afrika, Mei 1948 Hierdie artikel is ‘n indiepte ondersoek van die reaksie van die Britse regering en die Britse pers op die verkiesing van ’n Nasionale Party en apartheidsregering in SuidAfrika in Mei 1948. Die konvensionele standpunt – dat die verkiesing van 1948 ‘n “keerpunt” in Suid-Afrikaanse geskiedenis en Anglo-Suid-Afrikaanse verhoudinge verteenwoordig – word verwerp. In teenstelling, dit blyk dat die Britte, alhoewel hul feitlik eenvormig vir veldmaarskalk Smuts bewonder het en Afrikaner-nasionaliste gewantrou het, van mening was dat die uitslag van die 1948 verkiesing nie ‘n fundamentele verskuiwing was nie. Daar was ‘n wydverspreide siening in Brittanje en Suid-Afrika dat Smuts en die Verenigde Party spoedig weer in beheer sou wees and dat apartheid ’n onuitvoerbare politieke verleentheid vir die Nasionaliste sou wees. Eers na Smuts se dood in 1950 en na die verdere verstewiging van NP politieke beheer het die Britte begin aanvaar dat die herstel van ‘n matige progressiewe en proBritse bewind in Suid-Afrika nie sou plaasvind nie.